Correlation Analysis of Radical Polymerization Reactor Operating Conditions to Industrial Scale Swelling Capacity of Superabsorbent - Ilham, Willy Aulia; Kurniawan, Teguh; Saepurahman, Saepurahman; Aisyah, Ratna Sari siti (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Superabsorbent polymer (SAP) is a polymer that has one function as an absorbent material in baby diapers, whose quality is determined by the number of swelling capacity (SC). Many previous studies regarding the effect of synthesis parameters on the number of SC were limited to the laboratory scale, where the polymerization conditions, the number of variables, and SC data obtained were very limited, in contrast to the industrial scale. The radical polymerization stage, with its accompanying operating variables such as reaction temperature, monomer concentration, retention time, crosslinker concentration, the addition of nitrogen gas, and initiator concentration, affects the value of SC in industrial-scale production. This study aims to analyse the correlation between the reactor operating conditions and the number of SAP SC obtained. Correlation data analysis was done using Microsoft Excel with Data Analysis Toolpak and Python by utilizing production data with a total of 1,562 entries, where the correlation between each variable was calculated using Pearson’s correlation coefficient. The analysis determined that the variables that had the strongest correlation with the SC were retention time and reaction temperature, with correlation coefficient values of 0.31 and -0.26. The weakest correlation was obtained from the addition of nitrogen gas and an initiator with a value of -0.07 and -0.02. Positive values indicate a relationship that is directly proportional, while negative values indicate an inverse relationship. Based on the correlation analyses and trends, the ideal polymerization conditions have been identified.